Ontology of the Divinizing Grace according to the Defender of Hesychasm St. Gregory Palamas - Tselengidis, Dimitrios (Forum Theologicum Sardicense, 2025)
Dimitrios Tselengidis, Ontology of the Divinizing Grace according to the Defender of Hesychasm St. Gregory Palamas. The granting of divine grace for the salvation and deification of man is work of the God-man. Therefore, both the New Testament (2 Cor. 13:13) and the liturgical practice of the Church point to the grace of Christ. Divine grace is bestowed and manifested in creation through the incarnation of God, and in particular with His saving work (John 1:17). Each of the three persons of the Divine Trinity performs his own mission, but grace is given in a triune way, as it also happens with any other essential energy of the triune God.